Legendre’s Function and Additional Solution of a Weighted Heat Equation - ผิวอ่อน, ประภาส (KKU Science Journal, 2013)
In the article, a new simple method for solving solution of a weight heat equation is presented. The method bases on recursive relation and some property of Legendre’s function. Proof of the relation is also discussed.